Ginkgo biloba’s footprint of dynamic Pleistocene history dates back only 390,000 years ago - Hohmann, Nora; Wolf, Eva; Kiefer, Markus; Koch, Marcus (BMC genomics, 2018)
At the end of the Pliocene and the beginning of Pleistocene glaciation and deglaciation cycles Ginkgo biloba went extinct all over the world, and only few populations remained in China in relict areas serving as sanctuary for Tertiary relict trees. Yet the status of these regions as refuge areas with naturally existing populations has been proven not earlier than one decade ago. Herein we elaborated the hypothesis that during the Pleistocene cooling periods G. biloba expanded its distribution range in China repeatedly. Whole plastid genomes were sequenced, assembled and annotated, and sequence data was analyzed in a phylogenetic framework of the entire gymnosperms to establish a robust spatio-temporal framework for gymnosperms and in particular for G. biloba Pleistocene evolutionary history.
Published: 27 April 2018
Gesehen am 15.06.2018